Результаты предпроектных исследований по созданию новой конструкции выхлопного тракта газотурбинного компрессорного агрегата типа ГПА-Ц-16С - Ушаков, Сергей Михайлович; Каруцкий, Андрей Юрьевич; Щербаков, Олег Николаевич; Жуков, Сергей Анатольевич (НТУ "ХПИ", 2018)
В работе проведен анализ различных методов снижения выбросов загрязняющих веществ с выхлопными газами газотурбинных установок и основные ограничения по их применению. Выполнен анализ особенностей течения выхлопных газов в существующем выхлопном тракте для агрегата типа ГПА-Ц-16С с газотурбинным двигателем ДГ90Л2.1, в том числе с учетом закрутки потока на выходе из двигателя. Разработаны технические решения, обеспечивающие основные требования производителей систем каталитической очистки по неравномерности потока и требования производителя двигателя по величине потерь полного давления. Предложены технические решения, позволяющие заполнять утилизатор теплоты водой без останова газоперекачивающего агрегата.

This article summarizes the results of pre-design studies to reduce pollutant emissions of gas turbine compressor packages. The amount of pollutant emissions of compressor packages used at the Ukrainian gas transmission system as well as gas turbines manufactured by Ukrainian companies is presented. The main methods for reduction in pollutant emissions of gas turbines were analyzed. It was shown that one of the promising methods is to use special catalyst systems in the exhaust ducts. To select the catalyst location, a series of numerical simulations have been performed in the exhaust system of gas turbine compressor package GPA-C-16S type. It was shown that flow in the exhaust system has a complex structure mostly caused by features of the flow at the exhaust collector outlet. It was also found that swirling of the flow at the turbine outlet causes significant change of the flow at the exhaust system (18 % of the mass flow of exhaust gas moves along one of the wall and 82 % along another one). To prevent the degradation of the flow because of swirling at the turbine outlet the especially designed tongue was used at the exhaust collector. To reduce the overall non-uniformity of the flow the exhaust duct design with tubular straightener has been developed. To produce utility heat compressor packages of GPA-C-16S type can be equipped with heat recovery units, of between 3.5 to 9 MW. Their application allows achievement of thermal efficiencies of 0.36 to 0.46. The heat recovery units can contain several separate heat exchangers. Heat power control of the heat recovery units is carried out by heat exchangers on-off and by controlling the flow rate of exhaust gases through them. The design of the heat recovery units allows filling heat exchangers with water without shut-down of the gas turbine. To avoid high thermal stresses heat exchangers are cooled with atmospheric air supplied by fan of the heat recovery unit cooling system.
Results of pre-design studies on the development of a new design of the exhaust duct of the gas turbine compressor package GPA-C-16S type
Keywords: монооксид углерода; очистка каталитическая; газы выхлопные; скорость; поток; давление; выпрямитель; утилизатор теплоты; carbon monoxide; catalyst purification; exhaust scroll; flow uniformity; flow straightener; heat recovery unit